Influence of External Jet on Hydraulic Performance and Flow Field Characteristics of Water Jet Propulsion Pump Device - Jinxin Wu; Li Cheng; Can Luo; Chuan Wang (Shock and Vibration)
Water jet propulsion technology has broad application prospects in the field of ships, and water jet technology is a kind of high and new technology that is booming and has a wide range of applications. However, there are a few studies on the effect of the external jet on the performance of the water jet propulsion pump, and it is urgent to carry out this research. In this paper, the standard k-ε turbulence model is used to carry out the numerical simulation study of the influence of the external jet on the hydraulic performance and flow field characteristics of the water jet propulsion pump device. This paper discusses the selection of calculation models, the division of grids and the setting of turbulence models, and an in-depth analysis of the calculation results. The research results show that when a high-speed water jet enters a moving water body, it will cause turbulence in the moving water body. With the increase of jet flow, the turbulence phenomenon will be improved. The average velocity of the outlet section of the nozzle is consistent with the change of the total pressure. The average vortex gradually decreases, the turbulent kinetic energy changes little, the turbulence dissipation first decreases and then increases, and the nozzle axial force changes more and more. The axial force and thrust of the device will obviously increase when the two water streams merge and spray, and they will increase with the increase of the jet flow rate. By revealing the influence mechanism of the external jet on the water jet propulsion pump device, it can provide a theoretical basis and guiding direction for further optimizing the hydraulic performance of the entire device.